Solar-driven aromatic aldehydes: green production from mandelic acid derivatives by a Co(ii)/C3N4 combined catalyst in aqueous media. Issue 9 (14th February 2022) - Wu, Mi; Wang, Hongzhao; Mao, Haifang; Wang, Chaoyang; Dong, Zhenbiao; Tang, Ting; Zheng, Wei; Jin, Lehong; Liu, Jibo
Abstract : According to the requirements for sustainable development, reclaiming fine chemicals from wastewater under mild conditions is an extremely significant line of research. Abstract : According to the requirements for sustainable development, reclaiming fine chemicals from wastewater under mild conditions is an extremely significant line of research. A low-cost and high-efficiency polydentate chelate- and polymeric Co(ii )-based complex (Co-L)-loaded C3 N4 photocatalyst (Co-L/C3 N4 ) was constructed and used to convert aromatic mandelic acids in wastewater at room temperature. The BET specific surface area increased from 28 m 2 g −1 to 68 m 2 g −1, indicating its excellent absorptive character. The light absorption range of Co-L/C3 N4 reached 650 nm, while the band energy reduced to 2.30 eV, which caused a significant enhancement in photocatalytic activity. The conversion of substituted mandelic acids was more than 90% due to the photoactivity of Co-L/C3 N4 . Time-resolved PL spectra indicated the remarkable separation of the photogenerated electron–hole pairs in Co-L/C3 N4 . Furthermore, the UV-vis and in situ FTIR spectra indicated the formation of aldehyde groups in the selective oxidation process, which provided support for the plausible catalytic mechanism.